Bulgakov and Laboulaye (To the Issue of Sources of “Heart of a Dog”) - Alexandre F. Stroev (Литературный факт, 2022)
The article deals with the European literary tradition presenting the dog as a protagonist. The author claims that the magical story of the French politician and writer Édouard Laboulaye (1811 –1883) “The Poodle-Prince” (1867) is one of the literary sources for Mikhail Bulgakov’s novella “Heart of a Dog” (1925). The fact that Laboulaye was very popular in Russia in his time is confirmed by Laboulaye’s reception in the 1860s –1920s analysis presented in the article. Laboulaye’s work containing the dominant characteristics of the distopia and social and political satire influenced the texts of Alexander Kuprin, Evgeny Zamyatin as well. The fact that since the 1910s, “The Poodle Prince” has not been republished in Russia and the USSR, can probably explain that domestic Bulgakov's studies missed it as a source inspired “Heart of a Dog.”